Implementasi Metode Fuzzy Berbasis Arduino Mega 2560 dan Api Telegram untuk Peringatan Kebocoran Pipa - Tampubolon, Jhon Warisman; Primawan, A. B.; Sumarno, L. (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
The main ingredient for life on Earth is water. Every living thing on Earth cannot live without water. Springs can be found sporadically throughout Indonesia. Springs are usually found in hilly areas away from residential areas. Therefore, PDAM (Perusahaan Daerah Air Minum) oversees and manages the distribution of water to communities in Indonesia. In Indonesia, water loss during the distribution process through pipes often occurs, including underground pipes, is still a major problem. Leaks in distribution pipes that are difficult to locate are one of the causes of leakage. One potential answer to this problem is the advancement of Internet of Things technology, which is the development of a system that uses data from water flow sensors to find leaks in water pipes.This device can read, send, and display water discharge data and the number of pipe leaks, according to the findings from testing the entire system, this system can only detect leaks with a variation of 2 areas only, when detecting all three areas there is a failure in area 3.The network performance of this system has a delay of 2 seconds in the process of sending data to the application. For this purpose, an Arduino Mega 2560, ESP 8266-01, and a waterflow sensor are used to create an autonomous water flow discharge controller. These components are connected to send data to the Telegram application. Fuzzy logic is the method used by this device in its operation.